Business environment (Henry Stewart Talks, 2026)
Business environment definition and importance, Internal and external business environment elements, Impact of macro-environmental factors, Challenges in a dynamic and VUCA world, Risk management and resilience, Influence of competition and new entrants, Ethics, CSR, and sustainability